Christianity as distinct practices a complicated relationship - Henriksen, Jan-Olav 1961- (New York Bloomsbury T&T Clark, 2019)
"Jan-Olav Henriksen reconstructs and analyzes Christianity as a cluster of practices that manifest a distinct historically and contextually shaped mode of being in the world. Henriksen suggests that these practices imply a complicated relationship between the tradition in which they originate, the community that emerges from and is constituted by that tradition, and the individuals who appropriate the tradition that these communities mediate through their practices. Thus, to think of Christianity simply in terms of belief is misleading and represents an underdetermination of its distinct character. Henriksen further argues this relationship needs to be described primarily as practices aimed at orientation and transformation. His analysis points to Christianity's similarity to other religions in regard to the functional or pragmatic dimensions it displays. Examining facets such as prayer, the use of scripture, preaching and doctrine, Henriksen emphasizes that the element that makes a practice distinctively Christian is how it relates to and is informed by the Jesus story."--Bloomsbury Publishing
Acknowledgments INTRODUCTION -- Part I THEORY FOR UNDERSTANDING CHRISTIANITY AS PRACTICE -- 1. RELIGION AS ORIENTATION, TRANSFORMATION, AND LEGITIMIZATION OF HUMAN PRACTICES IN EVERYDAY LIFE 2. LIVED RELIGION INSTEAD OF RELIGION AS BELIEF 3. PRACTICES OF ORIENTATION AND TRANSFORMATION ARE SOCIAL PRACTICES 4. HOW FOCUS ON PRACTICES MAY RESHAPE PHILOSOPHY OF RELIGION 5. TO ACCESS THE WORLD AS WORLD: SEMIOSIS 6. RITUAL PRACTICES AS COGNITIVE PROSTHETICS 7. IN CONCLUSION -- Part II CHRISTIANITY RECONSTRUCTED: CLUSTERS OF PRACTICES SHAPED BY A STORY -- 8. (HI-)STORY AS RESOURCE FOR ORIENTATION AND TRANSFORMATION -- 9. THE CONTENT OF THE STORY: WHAT JESUS PRACTICED AS THE BASIS FOR (ECCLESIOLOGICAL) PRACTICE 10. A MORAL COMMUNITY THAT STEWARDS THE ABUNDANT GIFTS OF GOD -- 11. PRAYER AS MEANS OF TRANSFORMATION AND ORIENTATION: THE EXAMPLE OF THE LORD'S PRAYER -- 12. A REINTERPRETATION OF THE SCRIPTURES AND THE CONCRETE USE OF SCRIPTURE IN THE CHURCH -- 13. PREACHING AS A CONTEMPORARY PRACTICE: BETWEEN COMMUNICATIVE AND STRATEGIC ACTION -- 14. COMMEMORATION OF JESUS'S PRACTICES: OPENNESS TOWARD BOTH PAST AND FUTURE -- 15. PUZZLES FOR ORIENTATION: SUFFERING, DEATH, AND RESURRECTION -- 16. A THEOLOGICAL CONCLUSION: HOW TO PRACTICE "GOD"? -- 17. IS CHRISTIANITY A RELIGION? ARE BELIEF AND DOCTRINE OPPOSED TO PRACTICE? -- 18. CONCLUSION -- Bibliography -- Index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Includes bibliographical references and index
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Philosophical Theology; Christianity and culture; Christianity -- Philosophy; Theological Anthropology; Religion and sociology; Philosophical Theology; Christianity ; Rituals; Christianity and culture; Christian Sociology; Christian Life; Christianity ; Philosophy